The Gecko and Sticky. The greatest power - Van Draanen, Wendelin (Van Draanen, Wendelin. Gecko & Sticky, 2009)
When the diabolical Damien Black robs a bank and steals a tiger-eye of great sentimental value, he is pursued by thirteen-year-old Dave Sanchez and his sidekick, a talking gecko named Sticky, who are armed with a magical Aztec armband.